2015
DOI: 10.4254/wjh.v7.i5.761
|View full text |Cite
|
Sign up to set email alerts
|

Is hemodialysis a reason for unresponsiveness to hepatitis B vaccine? Hepatitis B virus and dialysis therapy

Abstract: Impaired renal function is associated with a high risk of chronicity of hepatitis B virus (HBV) infection. Patients on hemodialysis (HD) or peritoneal dialysis are at an increased risk of viral transmission due to frequent necessity of blood product transfer as well as use of contaminated dialysate or dialysis materials. Additionally, health professionals may cause viral spread via contaminated hands and carelessness against hygiene rules. The frequency of chronic HBV infection may be as high as 80% in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 72 publications
2
15
0
1
Order By: Relevance
“…Finally, we found no differences between responders and non-responders for parameters usually reported as factors of poor vaccine response [3,4,17,18]. Non-responder patients are older as previously reported in the literature [18,19], but the difference is not significant probably due to lack of power.…”
Section: Discussionsupporting
confidence: 45%
“…Finally, we found no differences between responders and non-responders for parameters usually reported as factors of poor vaccine response [3,4,17,18]. Non-responder patients are older as previously reported in the literature [18,19], but the difference is not significant probably due to lack of power.…”
Section: Discussionsupporting
confidence: 45%
“…The pathogenesis of this trait was recently reviewed by Sit et al 17 and has been attributed to a series of variables such as genetic characteristics, nutritional factors, vaccine dosages and route of administration, stage of CKD, diagnosis of diabetes mellitus, time on dialysis, dialysis adequacy, co-infection by HIV or HCV, and others.…”
Section: Discussionmentioning
confidence: 99%
“…There was no association between gender and the rate of the response to the HB vaccine. Different results have been reported for the relationship between these two variables in various studies, with positive correlations reported in some studies [9,[15][16][17] and negative correlations in some others [1,3]. These differences could be explained by intrinsic differences between men and women in their ability to respond to superficial hepatitis antigens.…”
Section: Discussionmentioning
confidence: 86%